Development of higher order thinking skill (HOTS) assessment instrument for salt hydrolysis - Alfi Rizkina Lubis; Ajat Sudrajat; Asep Wahyu Nugraha (Jurnal Pendidikan Kimia (JPKim), 2022)
This study aims to determine the results of the analysis of instrumentation requirements, the feasibility category of the Higher Order Thinking Skills an assessment instrument in terms of an expert validation. The research and the development model applied is 4-D (four-D) model.  The trial design consisted of content validation tests by experts and analyzed by Aiken's formula. The assessment instrument obtained 37 items that are suitable for use, which means the assessment instrument has met the content validity by the expert judgment which has been analyzed using Aiken's V of 0.85, which means that all items are valid.Keywords:4D model, HOTS, Instrument, Rasch model, Salt hydrolysis